Fables - Lobel, Arnold ([New York] : Harper & Row, Harper Trophy Book, 1980)
Twenty original fables about an array of animal characters from crocodile to ostrich.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
ALA Notable Books
Caldecott Medal/Honor
5.0
3-6
Keywords: Fables, American; Children's stories, American; Animals -- Fiction; Fables; Animals -- Fiction; Fables